62.0k views
3 votes
I would offer more points but i dont have anymore

I would offer more points but i dont have anymore-example-1
User LeonG
by
5.9k points

2 Answers

7 votes

1. 4x = -28

By dividing both sides of this equation by 4, we see that x = -7.

2. x - (-6) = -2

Note that x - (-6) is equal to x + 6. To solve the equation x + 6 = -2, subtract 6 from both sides to see that x = -8.

3. -x + 4 = -9

First, subtract 4 from both sides to get that -x = -13. Then, multiply both sides by -1 to see that x = 13.

4. -3x + 7 = 1

First, subtract 7 from both sides to get that -3x = -6. Then, divide both sides by -3 to see that x = 2.

4 votes

Answer:

1.) x=-7

2.) x= -8

3.) x=13

4.) x=2

Explanation:

ur lucky idc

User Anukul
by
6.0k points